1980
DOI: 10.3109/01050398009076331
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of a Double-Notch Audiogram

Abstract: Audiological findings in patients with histories of noise exposure were examined. 27 patients (1.5%) were found to have audiograms with a double-notch configuration. Information from their occupational history, medical history, and audiological findings was gathered and analysed. Their results were compared with those of 50 random samples of patients without the double-notch audiogram. Analyses suggest that the low frequency notch is probably also caused by noise damage. The low incidence of double-notch audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A similar "double-notch audiogram" has been reported in rare patients with noise exposure. 32 The HFSNHL in the older affected members in our study could be caused by the WFS1 mutation or may be merely superimposed on the LFSNHL secondary to noise or presbycusis. Because presbycusis and noise-induced hearing loss usually do not segregate in families as autosomal dominant traits and WFS1 mutations cause HFSNHL in patients with Wolfram syndrome, we hypothesize that the HFSNHL is part of the WFS1 phenotype.…”
Section: Commentmentioning
confidence: 67%
“…A similar "double-notch audiogram" has been reported in rare patients with noise exposure. 32 The HFSNHL in the older affected members in our study could be caused by the WFS1 mutation or may be merely superimposed on the LFSNHL secondary to noise or presbycusis. Because presbycusis and noise-induced hearing loss usually do not segregate in families as autosomal dominant traits and WFS1 mutations cause HFSNHL in patients with Wolfram syndrome, we hypothesize that the HFSNHL is part of the WFS1 phenotype.…”
Section: Commentmentioning
confidence: 67%
“…Before ascribing the variance in their hearing to a possible noise etiology, the issue of diagnosis of early NIHL should be discussed. A number of studies have used notching of audiograms, defined as a 10 dB or more elevation in PTT at 4 kHz as compared with neighboring frequencies, as an early indicator of NIHL 18 . Furthermore, some investigators have suggested that notching at 6 kHz may be an even earlier indicator of significant noise exposure 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used notching of audiograms, defined as a 10 dB or more elevation in PTT at 4 kHz as compared with neighboring frequencies, as an early indicator of NIHL 18 . Furthermore, some investigators have suggested that notching at 6 kHz may be an even earlier indicator of significant noise exposure 18,19 . However, NIHL is often diagnosed in the presence of a substantive elevation of the PTT in the 3‐ to 6‐kHz region in both ears in people with histories of ample exposure to hazardous noise levels.…”
Section: Discussionmentioning
confidence: 99%